A new species of Acanthoscurria Ausserer, 1871: proposal of the theraphosoides species-group and first published record of the genus from Colombia (Araneae: Theraphosidae) - Sherwood, Danniella; Gabriel, Ray; Peñaherrera-R., Pedro; García, Giraldo Alayón (Zootaxa, 2025)
A remarkable new species of Acanthoscurria Ausserer, 1871, is described from Colombia, Acanthoscurria armasi sp. nov., representing the first published record of the genus from this country. New insights into palpal bulb morphology and biogeography of the newly-proposed theraphosoides species-group are provided.